AIM/CD5L: a key protein in the control of immune homeostasis and inflammatory disease. Issue 2 (5th June 2015) - Sanjurjo, Lucía; Aran, Gemma; Roher, Nerea; Valledor, Annabel F; Sarrias, Maria-Rosa
Abstract : Review of involvement of CD5L protein in the modulation of inflammatory responses and its putative use as a biomarker of disease. Abstract: CD5L, a soluble protein belonging to the SRCR superfamily, is expressed mostly by macrophages in lymphoid and inflamed tissues. The expression of this protein is transcriptionally controlled by LXRs, members of the nuclear receptor family that play major roles in lipid homeostasis. Research undertaken over the last decade has uncovered critical roles of CD5L as a PRR of bacterial and fungal components and in the control of key mechanisms in inflammatory responses, with involvement in processes, such as infection, atherosclerosis, and cancer. In this review, we summarize the current knowledge of CD5L, its roles at the intersection between lipid homeostasis and immune response, and its potential use as a diagnostic biomarker in a variety of diseases, such as TB and liver cirrhosis.